A promoção da saúde no território Jardim Guanabara em Fortaleza – a espiritualidade como caminho - Silva, Max Cid Castelo Branco da (2017)
In this research we sought to reflect on the promotion of health in the territory, going through this path through spirituality - a place where the Popular Education in Health, with the qualitative approach and the methodology of the History of Life as a background. It focuses here the research of Health Promotion through spirituality, manifested through the practices of subjects who pray, bless, prescribe teas and herbs ancestrally used locally, and activate what the researcher calls Spiritual Experiences of Care and Healing (EECC). When entering the capture of the knowledge of the women who live and provide this kind of service in the Jardim Guanabara neighborhood in Fortaleza, it was concluded that by choosing spirituality as a way, it welcomes the power of popular culture and its production of knowledge about spirituality, focusing The subject in a more complete way, as being of biopsychosocial and spiritual dimensions. Focusing on the Spiritual Experience of Care and Healing, lived centrally by the mourners, a name that has been preserved historically and given to the coproducing subjects of health in the place that use the spiritual path, it was also concluded that the people who engage in this kind of Care and healing, are not so culturally colonized by the one-sidedness of the biological dimension, though they consider it alongside others, particularly the spiritual one. It was verified that when the Multiprofessional Residency in Family and Community Health (RMSFC) sought to enable a dialogue between the parents and the Basic Health Unit, the population welcomed this dialogic field, and health professionals, especially physicians, used this service Cooperatively. However, professionals who might be expected to be closer to the local culture after leaving RMSFC, and for lack of special treatment of this issue, were left with difficulties regarding interreligious dialogue and In the Health Unit has ended. It can also be concluded that, as health co-producers in the area, the rezadeiras have a wealth of understanding about the local daily life and its continuous transformations, and by giving a place of subject (not of object, in the service) To those who seek them, this perspective brings some empowerment to people's power to think in a more holistic way. The mourners, therefore, offer visibility to the unique experiences of transcendence, including those that include mediumship, and in dealing with knowledge about spirituality from the point of view of popular culture, offer a vision that expands as a total social fact (MAUSS, 1974) . It contemplates the collaboration of the areas of anthropossocial sciences and spiritist science, which calls itself the philosophical and religious aspect, as a collection that supports complex knowledge that associates physical healing with psychosocial and spiritual health.